PENGARUH PERCEIVED EASE OF USE, PERCEIVED USEFULNESS DAN TRUST TERHADAP REPURCHASE INTENTION MARKETPLACE - Paradita, Cokorda Nanda Putra; Ekawati, Ni Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.02.TAHUN.2024, 2024)
The phenomenon of online shopping on marketplaces has become commonplace in this digital age, partly due to the pandemic restrictions, as online shopping is more time-saving and efficient. One of the Indonesian marketplaces that operates in this field is Bukalapak. The purpose of this study is to explain the influence of perceived ease of use, perceived usefulness, and trust on repurchase intention. This research was conducted in Denpasar City with a sample of 112 respondents taken through purposive sampling and distributed using a Google form questionnaire with adjusted criteria measured by 16 indicators using a Likert scale. The data analysis technique used in this study is multiple linear regression analysis. The results of this study indicate that perceived ease of use has a positive and significant effect on repurchase intention, perceived usefulness has a positive and significant effect on repurchase intention, and trust has a positive and significant effect on repurchase intention. The results of this study indicate that the ease of use, usefulness, and trust provided by the Bukalapak marketplace to its customers can increase visits to the marketplace and cause customers to have a repurchase intention.